An Evaluation of the Effect of Consumer Characteristics on Retail Format Patronage Decisions - Mohammed Shaffiullah; Prof. T. Umamaheswara Rao (International Journal of Engineering and Management Research, 2018)
Consumer is prime factor in retailing. A customer can adapt various buying roles like initiator, influencer, decider, buyer, preparer, maintainer and disposer in purchasing and using the products. Buying behavior helps marketers learn the intensity and degree of involvement of customers in purchasing the products. Studies that link customer service to factors such as demographic, psychographic characteristics and store format choice are rather limited and under studied despite the fact of the discovery that individual characteristics of consumers influence their shopping behavior. Despite its importance and its contribution toward better understanding of consumer purchasing behavior, there is still lack of research in this area especially in the retail sector. In validating the measurements and investigating 650 questionnaires were filled by shoppers. The research concluded with a discussion on management implications as well as recommendations that suppliers should supply the good in shopping malls through considering their demographic and psychographic responses.